2011
DOI: 10.1021/ic201387d
|View full text |Cite
|
Sign up to set email alerts
|

Structural Chemistry, Monoclinic-to-Orthorhombic Phase Transition, and CO2 Adsorption Behavior of the Small Pore Scandium Terephthalate, Sc2(O2CC6H4CO2)3, and Its Nitro- And Amino-Functionalized Derivatives

Abstract: The crystal structure of the small pore scandium terephthalate Sc(2)(O(2)CC(6)H(4)CO(2))(3) (hereafter Sc(2)BDC(3), BDC = 1,4-benzenedicarboxylate) has been investigated as a function of temperature and of functionalization, and its performance as an adsorbent for CO(2) has been examined. The structure of Sc(2)BDC(3) has been followed in vacuo over the temperature range 140 to 523 K by high resolution synchrotron X-ray powder diffraction, revealing a phase change at 225 K from monoclinic C2/c (low temperature)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
47
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 30 publications
9
47
1
Order By: Relevance
“…Amino substituents on the terephthalate ligand are ordered, in contrast to the typical sitedisorder observed for ABDC ligands in other MOFs. 34,35 Ordering is consistent with the prominent role of the amino groups in linking the two networks via a 4-membered hydrogen-bonded ring motif (Figure 1c). The framework exhibits lozenge-shaped channels that lie along the a-axis, resembling those of aforementioned flexible MOFs such as MIL-53, although there is no pillar along the channel direction, but rather a helical arrangement of In(III) centres linked via ABDC ligands (Figure 1d).…”
Section: Resultssupporting
confidence: 72%
“…Amino substituents on the terephthalate ligand are ordered, in contrast to the typical sitedisorder observed for ABDC ligands in other MOFs. 34,35 Ordering is consistent with the prominent role of the amino groups in linking the two networks via a 4-membered hydrogen-bonded ring motif (Figure 1c). The framework exhibits lozenge-shaped channels that lie along the a-axis, resembling those of aforementioned flexible MOFs such as MIL-53, although there is no pillar along the channel direction, but rather a helical arrangement of In(III) centres linked via ABDC ligands (Figure 1d).…”
Section: Resultssupporting
confidence: 72%
“…Powder X-ray diffraction (PXRD) showed that 1 can retain framework integrity even after being heated at 673 K for 2 h (Supplementary Fig. S4), which is much higher than those for other organic and organic-inorganic hybrid solids showing large thermal expansion properties [4][5][6][7][8][9][10][11][12][13][14][15]21,22 . Gas sorption measurements showed that 1 cannot adsorb N 2 or O 2 at 77 K up to P/P 0 E1 but adsorb considerable CO 2 at 195 K, with an apparent Langmuir surface area of 188 m 2 g À 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, a few flexible PCPs showed much larger thermal expansion than common solids because the open coordination frameworks are relatively flexible [4][5][6][7][8][9][10][11][12][13][14][15] . Whereas small positive thermal expansion (PTE, 0oao20 Â 10 À 6 K À 1 , a and b V for axial and volumetric thermal expansion coefficients, respectively) is an intrinsic property of common solids 16 , negative (NTE, ao0 K À 1 ) [17][18][19][20] , very large (|a|4100 Â 10 À 6 K À 1 ), tunable and other special thermal expansion behaviours are extremely rare and have received considerable theoretical and practical interest [21][22][23][24] , which may be rationally realized by PCPs.…”
mentioning
confidence: 99%
“…The MOF can be dissolved and the functional groups become then observable ex situ by liquid-state NMR spectroscopy as described in [127,128,129,130,131]. On the other hand, the functional groups can be detected in situ by MAS NMR spectroscopy [42,132,133]. The advantage of the in situ method is its non-destructive character.…”
Section: Characterization Of the Mof Latticementioning
confidence: 99%
“…The coordination environment can be detected using chemical shifts and/or quadrupolar coupling constants for metal atoms such as 27 Al [107,108,144], 71 Ga [44], 45 Sc [46,132], and 6 Li [145]. Furthermore, metal atoms outside the MOF lattice, i.e.…”
Section: Characterization Of the Mof Latticementioning
confidence: 99%